Multiple perspectives on imprisonment in Europe - Diverse: Kjær Minke m.fl. (Nordisk Tidsskrift for Kriminalvidenskab)
There are currently over 1.6 million prisoners in Europe and conditions in European prisons vary widely. The European Society of Criminology’s Working Group on Prison Life and the Effects of Imprisonment was established in 2010. The Working Group consists of scholars from over 20 countries who aim to encourage prison research in Europe. These academics meet twice per year to discuss a variety of prison-related topics. The current article reviews some of the contributions to the Working Group’s meeting in Denmark in April 2016. It describes a broad selection of contemporary research on various aspects of the unique prison contexts found in different European countries. The contributions highlight a range of opportunities to improve conditions of confinement and to reduce recidivism after release.